DETEKSI ANEMIA DAN PENDAMPINGAN PADA ANAK ASUH - Surati Surati; SY Didik Widiyanto; Teguh Budiharjo; Nurul Qomariah (Jurnal LINK, 2018)
Ministry of Health in the Kirana (2011), showed patients with anaemia in adolescent girls and women amounted to 26.50% (WUS) 26.9%. In Central Java adolescents with relatively high anaemia reached 43.2% (Prov Health Profiles, Central Java, 2010). The number of incident cases of anaemia among students shows that the lack of nutrient consumption of iron (Fe) in adolescent girls. The objective of seeking out the health status of participants of community service after getting HB examination and found cases of anaemia in adolescent girls as a means for sustainable prevention. Benefits Service to the community is that as media early case finding for the management of anaemia in order to not become more severe through preventive measures such as health checks Hb. Community service execution activities conducted at two locations: at the Foundation and Pondok Pesantren Fatimatuzahro and Narun Najah pengabmas haemoglobin results by age group in the foundation and Darun Najah Pesantren is Fatimatuzahro and normal but the haemoglobin level Darun Najah better than difatimatuzahro. The conclusion of this devotion haemoglobin in foster care in both the Foundation and Pondok Pesantren is normal